2009
DOI: 10.4049/jimmunol.182.1.718
|View full text |Cite
|
Sign up to set email alerts
|

The CD70/CD27 Pathway Is Critical for Stimulation of an Effective Cytotoxic T Cell Response against B Cell Precursor Acute Lymphoblastic Leukemia

Abstract: For effective immunotherapy, maintaining the frequency and cytotoxic potential of effector cells is critical. In this context costimulation via the CD70/CD27 pathway has been proven essential. CD70 has been reported to be expressed to varying degrees on malignant B cells. However, in B cell precursor acute lymphboblastic leukemia, the most common childhood malignancy, the role of CD70 in stimulation of antileukemic T cell responses has so far not been delineated. Herein we demonstrate that in B cell precursor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…Nevertheless, expression of CD70 on tumor cells or antigenpresenting cells has also been described to have anti-tumoral effects (Arens et al, 2004;Bak et al, 2012;Couderc et al, 1998;Glouchkova et al, 2009;Kelly et al, 2002;Lorenz et al, 1999). This raises the question if CD70 blocking antibodies might also have the opposite effect on anti-tumoral immunity by blocking the stimulatory function of CD70 on antigen-presenting cells and NK cells or by depleting activated T cells, as suggested by the CD27-agonistic antibody, CDX-1127 (Thomas et al, 2014).…”
Section: Discussion: Are We Targeting the Right Molecule?mentioning
confidence: 97%
“…Nevertheless, expression of CD70 on tumor cells or antigenpresenting cells has also been described to have anti-tumoral effects (Arens et al, 2004;Bak et al, 2012;Couderc et al, 1998;Glouchkova et al, 2009;Kelly et al, 2002;Lorenz et al, 1999). This raises the question if CD70 blocking antibodies might also have the opposite effect on anti-tumoral immunity by blocking the stimulatory function of CD70 on antigen-presenting cells and NK cells or by depleting activated T cells, as suggested by the CD27-agonistic antibody, CDX-1127 (Thomas et al, 2014).…”
Section: Discussion: Are We Targeting the Right Molecule?mentioning
confidence: 97%
“…Consistent with this, work on CD8 ? T cells has demonstrated that the expansion of tumourspecific cytotoxic T lymphocytes (CTLs) is critically dependent on CD27 costimulation [63,64].…”
Section: Tnfr Superfamily Coreceptors In CD T Cell Activationmentioning
confidence: 99%
“…However, another soluble molecule belonging to the same TNF family, soluble CD40L (sCD40L), has been previously investigated and has been shown to play a costimulatory role in immune activation and regulation (12, 13). A recent study showed that a soluble form of CD27 (sCD27) shed by Waldenström's macroglobulinemia (WM) lymphoplasmacytic cells mediated up-regulation of CD40L and a proliferation-inducing ligand (APRIL) on WM mast cells (14), suggesting that sCD27 may act agonistically in the process of immune activation. This agonistic effect may help to break immunological tolerance of tumors.…”
Section: Introductionmentioning
confidence: 99%